Study of the correlation between red blood cell parameters in the patients with coronary heart disease and heart failure - Abdinur, Mohamed Abdirahman; Yong, Xie; Lingcai, Kong; Mohamud, Farah Abdidahir; Mohamud, Jamac Abdidahir; Ullahi, Sami (International Journal of Research in Medical Sciences, 2017)
Background: An increase of red blood cell distribution width (RDW) may have a certain effect to predict and evaluate the incidence and prognosis of coronary heart disease or chronic heart failure. Methods: Our retrospective study covered a total of 230 patients that were included due to a variety of indications for coronary angiography. Patients were defined into 2 categories; CAG (-) group (n=100), and CAG (+) group (n=130). The 2 groups were compared in order to investigate the differences between their RDW and other factors related and then further were sub-dived into 4 groups according to the NYHA functional class. Results: We observed that the patients in CAG (-) group 12.78±0.90; CAG (+) group 12.90±1.10 and had no significant difference in RDW. However higher RDW in patients with HF on all-cause was detected, 13.50±1.12 of group CAG (-)/NYHA II-IV and 13.39±1.31 of group CAG (+)/NYHA II-IV and there is statistical difference compared to group CAG (-)/NYHAI and group CAG (+)/NYHA I which were 12.80±0.47 and 12.87±0.69 respectively (P<0.001). There has no difference between the HF groups CAG (-)/NYHA II-IV and CAG (+)/NYHA II-IV group with (P=0.920), and no difference between groups without heart failure of (P=0.979). Conclusions: Although RDW had no predictive ability of coronary heart disease, but the elevation of RDW was highly and independently associated with chronic HF. Therefore, RDW can be clinically used as a parameter in risk stratification of patients with HF.